Diurnal variations in CO2 exchange fluxes and their influencing factors in a shallow macrophyte-dominated lake in the northeastern Qinghai-Tibetan Plateau: a case study of Hurleg Lake - Xie, Junxiang; Jin, Yanxiang; Jin, Xin; Li, Zi’ang; Zhang, Tongrui; Zhang, Xin; Yang, Jingyun (Frontiers in Plant Science, 2025)
As an important component of inland waters, shallow macrophyte-dominated lakes significantly influence regional carbon budgets. By using the static chamber-gas chromatography method and the sediment in-situ simulation, continuous fixed-point observations of CO2 exchange fluxes (F(CO2)) at water-air and water-sediment interfaces of shallow macrophyte-dominated Hurleg Lake were conducted. Combination with watershed meteorological conditions and lake water environmental parameters, their influencing factors were explored. The results revealed significant diel variations in F(CO₂) at both interfaces, characterized by peaks in the early morning and troughs in the evening or late night-a common feature of shallow macrophyte-dominated lakes. The composition of submerged macrophyte communities considerably affected the relative contribution of sediment-released CO₂ to the net atmospheric flux. The maximum contribution was observed in areas dominated by Potamogeton, followed by Myriophyllum zones, while the minimum occurred in Chara beds. Nocturnal F(CO₂) played a critical role in sustaining the carbon source function of the lake, accounting for 22.65%–42.90% of the total daily flux at the water-air interface and 5.57%-64.54% at the water-sediment interface across different vegetated and unvegetated zones. Neglecting nocturnal F(CO₂) would substantially increase uncertainties in estimating the lake’s overall carbon budget. The F(CO₂) at the water-air interface was primarily regulated by water temperature, pH, dissolved oxygen, and atmospheric pressure, whereas F(CO₂) at the sediment-water was mainly driven by porewater CO₂ concentration, sediment porosity, and water temperature.